ETUDE DU REGIME ALIMENTAIRE DE CARASSIUS CARASSIUS (LINNAEUS, 1758) - Zenati Meryem; Bouzenada Abir (My University, 2026)
This work deals with the study of the diet of a species of high commercial value which is the carasin, Carassius carassius (Linnaeus, 1758). Samples come from the Foum El-Khanga dam (Wilaya of Souk Ahras); sampling is spread over the month of February until April 2026 (monthly sampling of 63 specimens ) .The objective of our work is the qualitative and quantitative study of the diet of Carassius carassius, by analyzing stomach contents. It is important to note the absence of male individuals of Carassius carassius. Qualitative content analysis highlights a diversified diet with 308 prey items counted. Six different groups were identified, of algae, silt, plant debris, insects, copepods and daphnia. The global vacuity coefficient is Cv = 17.46%. The classification of ingested prey using the index of relative importance (% IRI) allowed algae, plant debris and vases to be classified as preferred foods. Daphnia and insects are ingested secondarily, whereas copepods are only accidentally found in the digestive contents. We indeed note that the individuals of C. carassius populating the Foum El-Khanga dam are omnivorous. ------------------------------------------------------------------------------------------------------------------------------------------------------------------------- يتناول هذا العمل دراسة النظام الغذائي لنوع ذو قيمة تجارية عالية وهو الكاراسيوس (ليناوس، 1758). تأتي العينات من سد فم الخنقة (ولاية سوق أهراس)؛ خلال الفترة الممتدة من شهر فيفري حتى أفريل 2026 (آخذ 63 من العينات شهريا). الهدف من عملنا هو الدراسة النوعية والكمية للنظام الغذائي لكاراسيوس، من خلال تحليل محتويات المعدة. ومن المهم أن نلاحظ غياب الأفراد الذكور من كاراسيوس. يسلط تحليل المحتوى النوعي الضوء على نظام غذائي متنوع يضم 308 فريسة تم إحصاؤها. تم التعرف على ست مجموعات مختلفة، من الطحالب والطمي وحطام النباتات والحشرات ومجدافيات الأرجل والدافنيا. معامل الفراغ العالمي هو Cv = 17.46%. سمح تصنيف الفرائس المبتلعة باستخدام مؤشر الأهمية النسبية (% IRI) بتصنيف الطحالب وبقايا النباتات والمزهريات كأطعمة مفضلة. يتم تناول دافنيا والحشرات بشكل ثانوي، في حين لا يتم العثور على مجدافيات الأرجل إلا عن طريق الخطأ في محتويات الجهاز الهضمي. ونلاحظ بالفعل أن أفراد C. carassius الذين يسكنون سد فم الخنقة هم من آكلي اللحوم والنباتات. ------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Ce travail porte sur l’étude de régime alimentaire d’une espèce à haute valeur commerciale qui est le carassin, Carassius carassius (Linnaeus, 1758). Des prélèvements proviennent au niveau de barrage de Foum El-Khanga (Wilaya de Souk Ahras), l’échantillonnage s’étale durant le mois de février jusqu’à le mois d’avril 2026(échantillonnage mensuelle de 63 spécimens). L’objectif de notre travail est, l’étude qualitative et quantitative du régime alimentaire du Carassius carassius, par l’analyse des contenus stomacaux. Il est important de signaler l’absence des individus mâles de Carassius carassius. L’analyse qualitative des contenus met en évidence un régime alimentaire diversifié avec 308 proies dénombrées. Six groupes différents ont été identifiés, d’algues, de vase, de débris de végétaux, d’insectes, de copépodes et de daphnies. Le coefficient de vacuité globale est de Cv = 17,46 %. Le classement des proies ingérées à l’aide de l’indice d’importance relative (% IRI) a permis de classer les algues, débris de végétaux et les vases dans la catégorie des aliments préférentiels. Les daphnies et les insectes sont ingérés secondairement alors que les copépodes ne sont rencontrés dans le contenu digestif qu’accidentels. Nous constatons en effet que les individus de C. carassius peuplant barrage Foum El-Khanga est omnivores.
Keywords: Foum El-Khanga dam; Carassius carassius; diet; stomach content; ecological indices; omnivore.; سد فم الخنقة، كاراسيوس، النظام الغذائي، محتوى المعدة، المؤشرات البيئية، الحيوانات آكلة اللحوم.; Barrage Foum El-Khanga; régime alimentaire; contenu stomacal; indices écologiques